Breed and timepoint-based analysis of chicken harderian gland transcriptome during Newcastle disease virus challenge - Vanamamalai, Venkata Krishna; Priyanka, E.; Kannaki, T. R.; Sharma, Shailesh (Frontiers in Molecular Biosciences, 2024)
Newcastle disease is a highly infectious disease caused by the Newcastle Disease Virus (NDV) and has a devastating financial impact on the global chicken industry. It was previously established that Leghorn and Fayoumi breeds of chicken exhibit variable resistance against NDV infection. The harderian gland is the less studied tissue of the chicken, known to play an essential role in the immune response. Our previous study reported differential gene expression and long noncoding RNAs (lncRNAs) between challenged and non-challenged chickens in the Harderian gland transcriptomic data. Now, we report the analysis of the same data studying the differential expression patterns between Leghorn and Fayoumi and between different timepoints during disease. Here, we observed a significant difference in gene expression between Leghorn and Fayoumi even in Normal conditions, and several immune-related genes were differentially expressed at initial stages. Apart from that, several non-immune genes were also differentially expressed. These genes and lncRNAs could play a role in Fayoumi being comparatively more resistant to NDV than Leghorn. Our study elucidated the importance of lncRNAs during the host defence against NDV infection, paving the way for future research on the mechanisms governing the genetic improvement of chicken breeds.